(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The literary and cultural movement known as modernism emerged in the early decades of thetwentieth century, particularly in the wake of World War I, and spread across the arts. The literature of theMovement is distinguished by its use of novel themes, structures, and ideas. The first works of modern artappeared in Europe’s major cities before making their way to the United States and Europe’s academiccenters. The beliefs of late nineteenth-century intellectuals like Freud, Marx, Darwin, and Nietzsche,together with the rapidly developing technologies of the time, form the foundation of modernism. RobertFrost gives ordinary things and events a special importance. He gives everyday occurrences a profoundsignificance. His poems always start with an image and conclude with a thought. The moral truth is atthe heart of all of his finest poetry. Oftentimes, he’ll utilize something ordinary as a metaphor to shedlight on some deeper, more universal truth in poetry.